ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA JURUSAN AKUNTANSI DALAM MEMILIH KARIR SEBAGAI AUDITOR (STUDI KASUS PADA MAHASISWA AKUNTANSI ANGKATAN TAHUN 2019 UNIVERSITAS WAHID HASYIM) - Kurniawati, Kurniawati (Journal of Mandalika Literature, 2022)
The purpose of this research is to find out the factors that influence the interest of students majoring in accounting class of 2019 at Wahid Hasyim University in choosing a career as an auditor. This research method is qualitative, the researcher carries out activities by describing data and facts by finding existing realities and is carried out continuously from the beginning to the end of the study. The results of this study found that the factors that influence the interest of accounting students class of 2019 to become audits are first salary, according to research results obtained from interviews with students majoring in accounting class of 2019 at Wahid Hasyim University that most Wahid Hasyim University students do not have a strong interest high to work as an audit, this is because the responsibility and workload as an audit is very high, so not many students are interested in working as an audit. Second, professional training, that most Wahid Hasyim university students do not really have a high interest in becoming an audit. This is because at Wahid Hasyim University itself there is no training to become an auditee. The absence of training will certainly cause most students not to be interested in working as an audit. The third is the availability of jobs, namely that job opportunities as audits can be found in the government sector as well as in the non-government sector. However, the interest in becoming an audit for accounting students class of 2019 at Wahid Hasyim University is not that high. This is because most students prefer to work in companies as admins or work in banks, because according to them the workload of being an audit is very large. The fourth work environment, that the interest of students majoring in accounting class of 2019 at Wahid Hasyim University to become an audit is not that great, this is because according to them to become an audit must work under pressure, besides that according to them the work environment cannot be relaxed, so this causes at least interest of students to work as an audit. Based on the analysis of the results of the research, it can be concluded that factors such as salary, professional training, availability of jobs and the work environment have not greatly increased the interest of accounting students from class of 2019 to become auditees.